SAT0127 Long-Term Safety and Efficacy Following the Administration of Multiple Rituximab Cycles in Rheumatoid Arthritis (RA) Patients: The Multicenter, Prospective Launch Study. (23rd January 2014) - Settas, L.; Andrianakos, A.; Aslanidis, S.; Boura, P.; Katsounaros, M.; Vassilopoulos, D.; Athanassiou, P.; Tempos, K.; Skarantavos, G.; Antoniadis, C.; Sakkas, L.; Andonopoulos, A. P.; et al.
Abstract : Background: About one third of RA patients do not initially respond to treatment with an anti-TNF agent whereas a similar rate demonstrates lack of efficacy over time. Rituximab/Mabthera administration (temporary B-lymphocyte depletion) is one of the therapeutic options for them. Objectives: The LAUNCH prospective study aimed at the evaluation of long-term efficacy and safety data following rituximab administration in standard clinical practice Methods: 17 Rheumatology sites in Greece enrolled 234 adult patients (63.0±12.4 years, 79.5% women) with severe RA and an inadequate response or non-tolerance to anti-TNF treatment. Rituximab (1gr) was administered IV on days 1 and 14 of each cycle, repeated every 6-12 months, for up to 7 cycles. Of these patients 41.2% and 56.2% had received one, or more, anti-TNF agent(s), respectively. Adverse events, DAS28, and the quality of life evaluation indices (Euroqol) were collected every 2 to 6 months for 5 years according to each site's standard clinical practice Results: During 496 patient/years, 28 adverse events /100 pt-yrs (including9.9 serious adverse events and 7.7 serious infectious per 100pt-yrs, respectively) were observed. Of the total number of adverse events a 46.7% was not related to rituximab. The mean number of adverse events per patient remained stable during repeated treatment cycles. Disease activity at baseline (mean±SD DAS28 of 5.36±1.40) was significantly reduced in cycles 1, 2, 3, 4, 5, and 6 by 1.34, 2.12, 2.25, 2, 56, 2.42 and 2.79, respectively (p<0.01). Compared to baseline, significant improvement in quality of life was also observed in all cycles (p<0.01) Conclusions: Rituximab administration in clinical practice for up to 5 years demonstrated an acceptable safety profile which was maintained over time. Likewise, maintenance and/or improvement of efficacy with repeated treatment cycles in patients with severe RA not responding to anti-TNF were evident Disclosure of Interest: L. Settas: None Declared, A. Andrianakos: None Declared, S. Aslanidis: None Declared, P. Boura: None Declared, M. Katsounaros: None Declared, D. Vassilopoulos: None Declared, P. Athanassiou: None Declared, K. Tempos: None Declared, G. Skarantavos: None Declared, C. Antoniadis : None Declared, L. Sakkas: None Declared, A. Andonopoulos: None Declared, V. Galanopoulou: None Declared, F. Solioti: None Declared, K. Boki: None Declared, E. Vritzali Employee of: Roche Hellas SA, P. Sfikakis: None Declared